2010
DOI: 10.1080/10503307.2010.492807
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between insight gained during therapy and long-term outcome in short-term dynamic psychotherapy and cognitive therapy for cluster C personality disorders

Abstract: This study examined whether 49 patients from a randomized controlled trial developed insight during therapy and whether insight predicted long-term outcome in short-term dynamic psychotherapy (STDP) and cognitive therapy (CT) for Cluster C personality disorders. Videotaped sessions early and late in treatment were analyzed using the Achievement of Therapeutic Objectives Scale. Patients' level of insight increased significantly during STDP but not CT. After controlling for early symptom change and early insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 17 publications
7
45
0
Order By: Relevance
“…This would be important as there is some dispute regarding the different relationship of insight to overall therapeutic change in CBT vis a vis other therapies, particularly psychodynamic therapy (e.g. Connolly Gibbons et al, 2009;Kallestad et al, 2010). Nevertheless, some of the characteristics identified as key to facilitating insight such as delivery of interpretations and consequent insight are related to successful outcomes in psychotherapy (Johansson et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…This would be important as there is some dispute regarding the different relationship of insight to overall therapeutic change in CBT vis a vis other therapies, particularly psychodynamic therapy (e.g. Connolly Gibbons et al, 2009;Kallestad et al, 2010). Nevertheless, some of the characteristics identified as key to facilitating insight such as delivery of interpretations and consequent insight are related to successful outcomes in psychotherapy (Johansson et al, 2010).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, improvement in another important dynamic therapy mechanism measure, namely reflective functioning, has been found to be associated with outcome of dynamic therapy for major depressive disorder (Bressi et al 2017) and borderline personality disorder (De Meulemeester et al 2017;Fischer-Kern et al 2015). Although full mediational analyses documenting change in the mechanism measure (i.e., the mediator) predicting subsequent outcome are rare for any psychotherapy, at least three studies have found that change in a dynamic mechanism measure (insight) predicts subsequent outcome of PDT (Connolly Gibbons et al 2009;Johansson et al 2010;Kallestad et al 2010). Thus, biases or "myths" towards PDT (Abbass et al 2017) are refuted by empirical data.…”
Section: Discussionmentioning
confidence: 99%
“…They offered new cause-effect relationships associated with certain emotional contents (cause), although this type of work was much more frequent towards the end of the therapy. Therefore, the patients were influenced by their therapists' actions, whose directive nature is revealed when co-constructing new meanings during the process (Kallestad et al, 2010), especially when there is sufficient evidence to suggest that clinical experience provides alternative meanings which promote therapeutic change (Wells, 1997). One of the main roles of therapists may be to help patients to use cognitive mechanisms (cause and tentative), not only for giving information about certain emotional contents (Affective Explorations), but also for resignifying this information (Affective Resignifications).…”
Section: Discussionmentioning
confidence: 99%